Analisis Konsep Ujrah Pada Sistem Pengupahan Karyawan PT RHF Malang Melintang Di Lawang-Kabupaten Malang - Maulidiyah, Dewi Sari; Sukamto, Sukamto; Aslikhah, Aslikhah (Jurnal Iqtisaduna, 2024)
Ujrah is the payment of salary or wages promised by the first party to the second party based on the work that has been done or the results of that work. This concept emphasizes that ujrah is a reward for the work a person has done. In the context of muamalah fiqh, transactions between money and human labor are referred to as ujrah or wages. In the perspective of Islamic law, wages (ujrah) are a right obtained by individuals who have worked, and it is the employer's obligation to pay them. Wage regulation is included in the ijarah category in muamalah fiqh. Sources of Islamic law that serve as guidelines for resolving various wage problems include the Al-Qur'an, Hadith, and Ijma', as well as various other relevant legal sources. This research aims to evaluate the concept of ujrah as the basis for an employee wage system in a company context, taking into account Islamic principles and state legal policies. The research method used is a qualitative approach with a descriptive approach. Research instruments include observation, interviews and documentation. The research results show that payments to workers are adjusted to their respective fields of work. Fairness in wage payments is considered important, where workers must receive wages fairly and adequately. According to employees, the principle of fairness in paying wages is when there is no difference in treatment between one employee and another based on the work they do. Based on these results, it can be concluded that the wages received by employees are in accordance with the agreement that has been made. Keywords: Ujrah concept, Ujrah, wages, wage system.